Manajemen Pemasaran Dalam Meningkatkan Mutu Pendidikan - Wawan Hari Subagyo (Lembaga Pengembangan Kinerja Dosen, 2024)
Marketing is an activity that sells and offers products and services that are owned, so that consumers can buy and enjoy the products offered. In the current era of globalization, competition between educational institutions is increasingly attractive and competitive, therefore good marketing activities are needed in order to build a positive image and attract public interest. The